2019
DOI: 10.1016/j.celrep.2019.07.104
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for ATP-Hydrolysis-Driven DNA Translocation by the CMG Helicase of the Eukaryotic Replisome

Abstract: SummaryIn the eukaryotic replisome, DNA unwinding by the Cdc45-MCM-Go-Ichi-Ni-San (GINS) (CMG) helicase requires a hexameric ring-shaped ATPase named minichromosome maintenance (MCM), which spools single-stranded DNA through its central channel. Not all six ATPase sites are required for unwinding; however, the helicase mechanism is unknown. We imaged ATP-hydrolysis-driven translocation of the CMG using cryo-electron microscopy (cryo-EM) and found that the six MCM subunits engage DNA using four neighboring prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
121
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(156 citation statements)
references
References 72 publications
20
121
0
Order By: Relevance
“…A recent cryo-EM structure of yeast CMG, where translocation on a fork DNA substrate is blocked by biotin-streptavidin barriers, exhibited a short stretch of dsDNA enclosed by the Nterminal zinc finger (ZF) protrusions of Mcm2-7 . In a similar assay, we showed that the N-terminal end of MCM in Drosophila CMG interacts with parental DNA at the fork in an analogous manner (Eickhoff et al, 2019) suggesting that the mode of helicase engagement with DNA is conserved between Drosophila and yeast. A possible exit route for the displaced lagging-strand template was proposed to be formed by cavities between MCM ZF protrusions (Eickhoff et al, 2019, Li andO'Donnell, 2018).…”
Section: Cmg Bypasses a Protein Directly Crosslinked To The Excluded mentioning
confidence: 81%
See 2 more Smart Citations
“…A recent cryo-EM structure of yeast CMG, where translocation on a fork DNA substrate is blocked by biotin-streptavidin barriers, exhibited a short stretch of dsDNA enclosed by the Nterminal zinc finger (ZF) protrusions of Mcm2-7 . In a similar assay, we showed that the N-terminal end of MCM in Drosophila CMG interacts with parental DNA at the fork in an analogous manner (Eickhoff et al, 2019) suggesting that the mode of helicase engagement with DNA is conserved between Drosophila and yeast. A possible exit route for the displaced lagging-strand template was proposed to be formed by cavities between MCM ZF protrusions (Eickhoff et al, 2019, Li andO'Donnell, 2018).…”
Section: Cmg Bypasses a Protein Directly Crosslinked To The Excluded mentioning
confidence: 81%
“…It is not clear whether the recent CMG structures in complex with fork DNA exhibiting dsDNA within the MCM ZF domains represent the helicase in an active fork unwinding state or a paused state (Eickhoff et al, 2019;Georgescu et al, 2017). Because CMG can unwind dsDNA much more efficiently with the help of RPA, a high-resolution structure of CMG while unwinding duplex DNA in the presence of RPA should further elucidate how the helicase engages with DNA in the eukaryotic replisome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A complicating feature when trying to analyse CMG translocation is that, unlike the homohexameric helicases of simpler organisms, the MCM2-7 motor of the CMG is a hetero-hexamer of six related but distinct subunits (Bochman, Bell, & Schwacha, 2008). Indeed, biochemical measures of DNA unwinding by purified fly CMG showed that ATP binding and hydrolysis are not equally important at all MCM ring interfaces (Eickhoff et al, 2019;Ilves, Petojevic, Pesavento, & Botchan, 2010). Furthermore, biological evidence in yeast shows that the importance of DNA binding is different among MCM subunits (Lam et al, 2013;Ramey & Sclafani, 2014).…”
mentioning
confidence: 99%
“…Recent cryoEM analyses of yeast CMG have led to the proposal of alternative translocation mechanisms, based on 'pumpjack' or 'inchworm' movements of the N-and Ctier of the MCM ring (Abid Yuan et al, 2016). A recent structural study of the fly CMG in conditions of DNA-fork unwinding (Eickhoff et al, 2019) imaged four distinct states of the helicase; the states formed the basis for an asymmetric model of DNA unwinding that accounted for the different roles of the MCM2-7 subunits in translocation.…”
mentioning
confidence: 99%